The Role of Destination Image and City Branding in the Decision of Singaporeans to Visit Batam City (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This study aims to analyze the role of destination image and city branding on the decision of Singaporeans to visit tourist attractions in Batam City. This study uses a quantitative method with a survey approach. The number of samples used in this study was 100 Singaporeans. Data was obtained through the distribution of questionnaires to Singaporeans who have visited or plan to visit Batam City. The data analysis technique used was multiple regression analysis to determine the influence of each variable on the decision to visit. The results of the study show that the image of the destination has a significant influence on the decision to visit, where the positive perception of natural beauty, facilities, and community friendliness is the main attraction. City branding also plays an important role in increasing the awareness and interest of Singaporeans in Batam, especially through the promotion of slogans, city icons, and international events. The study concludes that the combination of a strong destination image, consistent city branding promotion, will be able to increase Singaporeans' decision to visit Batam.